Pemetaan profil psikologis atlet Nusantara Petanque Club Kediri sebagai dasar pengembangan program pembinaan mental - Moch Yunus; Sapto Adi; Abdian Asgi Sukmana; Ulma Erdilanita (Darmabakti: Jurnal Pengabdian kepada Masyarakat, 2025)
This community service activity was motivated by a problem faced by the Nusantara Petanque Club Kediri, namely the lack of comprehensive mapping of athletes' psychological profiles as a basis for developing mental training programs. This situation has led coaches to continue relying on general approaches that fail to address the psychological needs of individual athletes. This activity aims to map the psychological profiles of Petanque athletes, covering six main components, namely concentration, resilience, self-efficacy, mental toughness, anxiety, and decision-making, as a first step in strengthening the mental capacity of athletes. The community service was conducted on October 25, 2025, at the Nusantara Petanque Club Kediri training facility, involving 14 active athletes. The implementation method employed a survey-based community service approach, involving the stages of coordination, socialization, completion of standardized psychological instruments, and quantitative descriptive data analysis using frequency distribution. The results of the study indicate that mental toughness, self-efficacy, and resilience fall into the high category, while decision-making tends to be moderate, and concentration is relatively low. These findings confirm that Petanque athletes' mental preparedness is quite strong, but there is a need to improve their ability to focus and make decisions under pressure. This activity contributes to providing an empirical basis for coaches to develop more specific, measurable, and sustainable psychological training programs.